IMPLEMENTATION OF A DIFFERENTIATED LEARNING MODELS TO IMPROVE STUDENT’S LEARNING ABILITY IN LOCAL CULTURE MATERIAL - Fatur Rahmah; Ade S Anhar; Ahmadin (El Midad, 2025)
SDIT Insan Kamil Bima City, it is known that students are not fully accustomed to the application of differentiated learning models, especially in local cultural materials. This shows that diverse learning styles among students have not been fully accommodated in the learning process. This study aims to analyze the implementation of differentiated learning models to improve students' learning ability in local cultural materials at SDIT Insan Kamil Bima City. The research method uses a qualitative approach with case study techniques, which involve observation, interviews, and documentation. The results of the study show that the application of a differentiated learning model, especially through content and process differentiation, is able to increase students' engagement and understanding of local cultural materials. One of the effective strategies used is an educational visit to the BOJO Breast Milk Museum, where students can directly observe and experience the local culture. This approach shows a significant increase in student understanding, with maximum achievements. In addition, differentiated learning allows teachers to tailor teaching methods to students' individual learning styles, interests, and readiness, which contributes to increased motivation and learning outcomes. Nonetheless, challenges such as classroom commotion and difficulty recognizing students' learning styles remain obstacles that need to be overcome with teacher creativity and innovation. Thus, the implementation of differentiated learning has proven to be effective in supporting the Independent Curriculum and developing the unique potential of each student.